A Modern Peace? Schumpeter, the Decline of Conflict, and the Investment–War Trade-Off. (December 2016) - Chatagnier, J. Tyson; Castelli, Emanuele
Drawing on the writings of Joseph Schumpeter, we develop and explore a new theory of international conflict. We outline a simple mechanism whereby industrialization fosters peace, suggesting that industrialized states are more peaceful because they can gain more by investing at home than by pursuing foreign military conquest. We borrow from Schumpeter to argue that our mechanism is distinct from traditional measures of liberalism. Empirically, we propose a measure of industrial development, based on a state's economic structure. Using World Bank sector-specific economic data, our exploratory analysis shows that a more industrialized economy significantly reduces the likelihood that a state will be involved in a fatal military conflict. We show that this result is robust across a number of model specifications and independent of both democracy and capitalism. We propose this as an interesting first step toward a broader research program on modernization and conflict.